Design Information System of Recrutment at PT. XYZ - setiawan; Arif, Muhamad (ASIAN PUBLISHER, 2023)
Recruitment System At PT. ZYX uses an inefficient system, where applicants apply for vacancies via WhatsApp. Some people think that vacancies that must apply via WhatsApp are characteristics of fraudulent vacancies. Therefore we need a web-based recruitment information system. With a web-based system, applicants will have more confidence in vacancies and also make it easier for the recruitment team to process applicant data, because when applicants apply for vacancies, applicant data will enter the database, so the recruitment team does not need to manually input applicant data into the database.In research on the design of the recruitment information system using literature and field studies using the PHP Framework programming language, MySQL Database, designing the user interface using HTML, CSS and Javascript and conducting program trials in the final stages of creating a web-based recruitment information system.The results of this study conclude that a web-based recruitment information system has been designed and tested at PT. Impact Power Mandiri which can produce information regarding the management of applicant data, vacancy data, applicant status data and create web-based recruitment reports optimally and efficiently.